2023
DOI: 10.3389/fcvm.2023.1243867
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a causal relationship between ankylosing spondylitis and cardiovascular disease: a two-sample Mendelian randomization study

Yan Zhong,
YingWen Chen,
XinYue Zhang
et al.

Abstract: ObjectiveObservational studies have suggested an increased risk of cardiovascular disease in individuals with ankylosing spondylitis. However, these studies are prone to confounding factors and reverse causality. To address these limitations, we conducted a Mendelian randomization study to assess the causal relationship between AS and CVD.MethodsThe study population comprises 9,069 individuals with ankylosing spondylitis and 509,093 individuals with either of six common cardiovascular diseases and a related in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…However, the mechanism behind this association is still unclear. Research has shown elevated levels of pro-inflammatory cytokines such as IL-6 and CRP in AS (Zhong et al, 2023), suggesting that inflammation may play a role. Studies have shown that AS can lead to obliterative endarteritis in small vessels supplying the atrioventricular node and the aortic root, leading to a prolongation of the PQ interval and an increased risk of atrial fibrillation, first-degree atrioventricular block, and aortic valve insufficiency (Haroon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism behind this association is still unclear. Research has shown elevated levels of pro-inflammatory cytokines such as IL-6 and CRP in AS (Zhong et al, 2023), suggesting that inflammation may play a role. Studies have shown that AS can lead to obliterative endarteritis in small vessels supplying the atrioventricular node and the aortic root, leading to a prolongation of the PQ interval and an increased risk of atrial fibrillation, first-degree atrioventricular block, and aortic valve insufficiency (Haroon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism behind this association is still unclear. Research has shown elevated levels of pro-inflammatory cytokines such as IL-6 and CRP in AS (Zhong et al, 2023), suggesting that inflammation may play a role. Studies have shown that AS can lead to obliterative endarteritis in small vessels supplying the atrioventricular node and the aortic root, leading to a prolongation of the PQ interval and an increased risk of atrial fibrillation, first-degree atrioventricular block, and aortic valve insufficiency (Haroon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism behind this association is still unclear. Research has shown elevated levels of pro-inflammatory cytokines such as IL-6 and CRP in AS (Zhong et al, 2023), suggesting that inflammation may play a role. Studies have shown that AS can lead to obliterative endarteritis in small vessels supplying the atrioventricular node and the aortic root, leading to a prolongation of the PQ interval and an increased risk of atrial fibrillation, first-degree atrioventricular block, and aortic valve insufficiency (Haroon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%